The reverse irony of Monique Proulx's Le sexe des etoiles - Arseneau, Veronique (Romanica Olomucensia, 2019)
This paper proposes an analysis of the irony in the metafeminist novel Le sexe des etoiles by the Quebec author Monique Proulx. The irony presents itself in multiple ways, but especially by the presence of several narrative voices, creating ironic re-readings of the novel. Using the theories of irony and sarcasm of Hutcheon and Duval and Martinez, this paper lists the various ironic procedures at work in Proulx's novel. It also explores how the narration of Le sexe des etoiles is exponentially ironic with the help of Bakhtine's polyphony theory. Hence, it is possible to state that a re-reading based on the narrative voices creates a reverse irony, which can only be discovered by the reader at the end of the story. The study of the ironic forms of Le sexe des etoiles reveals that Proulx's novel is indeed an ironic and critical novel about 1980s Quebec. The analysis of polyphony in the novel also reveals Proulx's play with her alleged authors within the story. This narrative form accentuates the irony and the criticism revealed in the various voices within Proulx's work. The novel is thus constructed as an ironic criticism of its time by using various ironic and satirical methods, but it is by this complex and twisted narration that Proulx's novel manages to fool its reader.
Keywords: Monique Proulx; Le sexe des etoiles; irony; polyphony; satire; narrative voices